(untitled) (Swiss Medical Weekly, 2012)
QUESTIONS UNDER STUDY: Up to 20% of elderly patients present to the emergency department (ED) with non-specific complaints (NSC), such as “generalised weakness”, the majority suffering from serious conditions requiring timely intervention. Little is known about the use and influence of diuretics and renin-angiotensin-aldosterone (RAAS) blockade on morbidity in those patients. The hypothesis was tested that the use of diuretics and RAAS blockade could be associated with an increased incidence of serious conditions in those patients. METHODS: During a 23-month period, all adult non-trauma patients with an Emergency Severity Index (ESI) of 2 or 3 were prospectively enrolled. Serious conditions were defined as potentially life-threatening conditions or conditions requiring early intervention to prevent further morbidity and mortality. RESULTS: Study population consisted of 633 patients with median age 82 years, median Charlson comorbidity index 2. 59% of all subjects suffered from a serious condition. 299 subjects (47.2%) used diuretics, of which 65.6% suffered from a serious condition. Combination therapy of RAAS blockade and diuretics was found in 158 subjects (24.9%), 70.3% of which suffered from a serious condition. The intake of two or more diuretics, loop diuretics and a combination therapy with diuretics and RAAS blockade were associated with an increased risk for serious condition (p = 0.036; p = 0.021; p = 0.004). CONCLUSIONS: Treatment with two or more diuretics, loop diuretics, or a combination therapy with RAAS blockade and diuretics are independently associated with serious condition and therefore should be recognized as “red flags” in elderly patients presenting to the ED with NSC.